2004
DOI: 10.1017/s0031182003004281
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the access of albendazole, fenbendazole and triclabendazole toFasciola hepatica: effect of bile in the incubation medium

Abstract: The work reported here describes the comparative ability of albendazole (ABZ), fenbendazole (FBZ) and triclabendazole (TCBZ) to penetrate through the tegument of mature Fasciola hepatica, and the influence of the physicochemical composition of the incubation medium on the drug diffusion process. The data obtained from the trans-tegumental diffusion kinetic studies were complemented with the determination of lipid-to-water partition coefficients (octanol-water) for the benzimidazole (BZD) anthelmintic drugs ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
(50 reference statements)
8
23
0
Order By: Relevance
“…Only 7.4 % of drug available in ovine bile was able to diffuse into the parasite. Similar results were previously described by Alvarez et al (2004) starvation (Skuce and Fairweather, 1990). In addition, CLS reduces the availability of ATP, needed (for example) for the energy-demanding processes of gametogenesis and oogenesis, and it has been associated in cattle with a decrease in parasite egg production (Hanna et al, 2006).…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 1 more Smart Citation
“…Only 7.4 % of drug available in ovine bile was able to diffuse into the parasite. Similar results were previously described by Alvarez et al (2004) starvation (Skuce and Fairweather, 1990). In addition, CLS reduces the availability of ATP, needed (for example) for the energy-demanding processes of gametogenesis and oogenesis, and it has been associated in cattle with a decrease in parasite egg production (Hanna et al, 2006).…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…The acquisition of broad-spectrum anthelmintics by liver flukes could be by passive diffusion through their tegument (Alvarez et al, 2000(Alvarez et al, , 2001. However, drug diffusion depends on different factors, such as molecule lipophilicity, molecular size, concentration gradient, surface area of contact between drug and parasite (Mottier et al 2006) and the physico-chemical properties of the surrounding parasite environment (Alvarez et al, 2004). Clearly, under ex vivo conditions, the presence of bile modified the diffusion and accumulation of CLS into the parasite, decreasing it by 72 % compared with that observed after incubation in RPMI medium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…While the FMO system was found as the main enzymatic pathway involved in the sulphoxidation of TCBZ (yielding ∼77% of TCBZSO production), both enzymatic systems participate in a similar proportion in the sulphonation reaction to form the sulphone metabolite. Studies on ex vivo drug diffusion into TCBZ‐susceptible Fasciola hepatica , demonstrated that TCBZ, TCBZSO and TCBZSO 2 have the capability to penetrate the fluke′s tegument (Alvarez et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The tegument plays an important role in the uptake of nutrients such as glucose and amino acids into the liver fluke, in addition to roles in sensory perception, osmoregulation and protection against the host's immune response, for example (Fairweather et al 1999). The tegument of trematode and cestode parasites has been shown to be the primary site of anthelmintic entry (Alvarez et al 2000, 2001, 2004, 2007; Mottier et al 2003, 2006 a ). Similarly, the cuticle has been demonstrated as an important interface of drug uptake in nematodes (Ho et al 1990; Sims et al 1996; Cross et al 1998).…”
Section: Introductionmentioning
confidence: 99%